2017
DOI: 10.12669/pjms.334.12926
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric inflammatory bowel disease: Clinical presentation and disease location

Abstract: Objective:To determine different clinical presentationsand disease location demarcatedby upper and lower gastrointestinal endoscopyand relevant histopathologyin children diagnosed with inflammatory bowel disease (IBD).Methods:This is 5 years (2010 to 2015) retrospective studyconducted at the Aga Khan University Hospitalenrolling65admitted children between 6 months to 15years from either gender, diagnosed with IBD on clinical presentation, endoscopy and biopsy. Different clinical presentations at the time of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…5 Similar to our study where only major EIMs were considered, oral manifestations were not considered as a major EIMs in other studies. 2,3,6,7 In our study, if we added minor EIMs, the prevalence would reach 28.8%. 2…”
Section: Dear Editormentioning
confidence: 56%
See 2 more Smart Citations
“…5 Similar to our study where only major EIMs were considered, oral manifestations were not considered as a major EIMs in other studies. 2,3,6,7 In our study, if we added minor EIMs, the prevalence would reach 28.8%. 2…”
Section: Dear Editormentioning
confidence: 56%
“…4 A study from Hungary reported EIMs in 30% of 331 patients with Crohn’s disease (CD), another study from Pakistan reported EIMs in 7% of 56 patients with IBD. 4,6 Defining the true prevalence of EIMs in patients with IBD is difficult. 3 Differences in study designs and methodology might explain the variation in the prevalence of EIMs.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with UC tend to present with recurrent abdominal pain, rectal bleeding, and bloody diarrhea, while patients with CD may present with extraintestinal manifestations such as poor growth, weight loss, musculoskeletal diseases, hepatobiliary diseases, ocular diseases, and renal diseases. Endoscopic findings of UC tend to be more of a uniformly diffuse inflammation of the gut that involves the mucosa and submucosa, while CD typically shows patchy (skip) lesions, transmural gut involvement with or without abscesses, and granulomas [2][3]. The etiology of IBD, though not fully elucidated, is believed to be multifactorial and results from an interplay of genetic predisposition, environmental factors, and immune dysregulation, which ultimately results in chronic inflammation of the gut [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic findings of UC tend to be more of a uniformly diffuse inflammation of the gut that involves the mucosa and submucosa, while CD typically shows patchy (skip) lesions, transmural gut involvement with or without abscesses, and granulomas [2][3]. The etiology of IBD, though not fully elucidated, is believed to be multifactorial and results from an interplay of genetic predisposition, environmental factors, and immune dysregulation, which ultimately results in chronic inflammation of the gut [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%